2020
DOI: 10.1177/1097184x20910474
|View full text |Cite
|
Sign up to set email alerts
|

“He Should Learn That He Cannot Get a Woman for free”: Male Elopers and Constructions of Masculinity in the Afghan Justice System

Abstract: This article explores constructions of gender, masculinity, and class in moral crimes prosecutions, and their legal aftermaths in Afghanistan. It argues that the lack of attention to men in advocacy and research about moral crimes, while reflecting a (geo-) politicized conflation of gender with women, constitute both an empirical and an analytical oversight. The first part of the article discusses the legal grounds for the prosecution of men for “moral crimes” in Afghanistan and presents statistical data that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
(9 reference statements)
0
2
0
Order By: Relevance
“…As research has shown, the lived reality of Afghan Turkmen is much more complex and elopement marriages, an un-prestigious route to marriage often chosen by persons of lower social status, 20 are not unheard of among Turkic language speaking communities in Northern Afghanistan (Wimpelmann, Hakimi, and Saadat 2020). However, due to its lower social status, this model of marriage may neither be desirable nor easily accessible to migrant men who have families in Afghanistan and work in Turkey.…”
Section: 'Good Men Don't Elope!'mentioning
confidence: 99%
“…As research has shown, the lived reality of Afghan Turkmen is much more complex and elopement marriages, an un-prestigious route to marriage often chosen by persons of lower social status, 20 are not unheard of among Turkic language speaking communities in Northern Afghanistan (Wimpelmann, Hakimi, and Saadat 2020). However, due to its lower social status, this model of marriage may neither be desirable nor easily accessible to migrant men who have families in Afghanistan and work in Turkey.…”
Section: 'Good Men Don't Elope!'mentioning
confidence: 99%
“…Afghan men are entrusted with safeguarding their family's honour, often expressed through exerting control over female family members ( Moghadam, 1992 ). Afghan men are perceived as masculine when they protect and provide for their female dependents ( Wimpelmann et al., 2020 ). Patriarchal tribal customs override religious texts, particularly related to education.…”
Section: Introductionmentioning
confidence: 99%